2011
DOI: 10.1080/01431161.2011.627391
|View full text |Cite
|
Sign up to set email alerts
|

Reference spectra to classify Amazon water types

Abstract: Reference spectra extracted from spectral libraries can distinguish different water types in images when associated with limnological information. In this study, we compiled available databases into a single spectral library, using field water reflectance spectra and limnological data collected by different researchers and campaigns in the Amazonian region. By using an iterative clustering procedure based on the combination of reflectance and optically active components (OACs), reference spectra representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 39 publications
1
7
0
2
Order By: Relevance
“…At the end of the dataset sensor simulation, the quantized noiseless water leaving radiance for each band L b w (B n ) and L * b w (B n ) were converted to R rs (B n ) according to Equation (11), in order to be used as the input for bio-optical algorithms.…”
Section: Of 18mentioning
confidence: 99%
“…At the end of the dataset sensor simulation, the quantized noiseless water leaving radiance for each band L b w (B n ) and L * b w (B n ) were converted to R rs (B n ) according to Equation (11), in order to be used as the input for bio-optical algorithms.…”
Section: Of 18mentioning
confidence: 99%
“…The spatial-temporal monitoring of changes in water composition for Amazon floodplains at regional scale is challenging and has not been effectively achieved by the current remote sensing technologies. A few studies have demonstrated empirical relations between surface reflectance and OACs of Amazonian water bodies (e.g., Barbosa et al, 2010;Ferreira, Barbosa, Novo, & de, 2012;Lobo, Novo, Barbosa, & Galvão, 2012;Novo, Filho, & Melack, 2004;Rudorff, Galvão, & Novo, 2009), but the seasonal variation in range of OAC concentrations is such that empirical relations are limited to remote sensing applications at similar hydrological phases. Development of universal algorithms requires further detailed investigations of the underwater light field in Amazon floodplain waters, which are almost inexistent in the literature.…”
Section: Introductionmentioning
confidence: 98%
“…The three centroid sets corresponding to Classes 1-3 included 8, 28, and 26 samples, respectively. The method presented here and the study by Moore et al [1,24] are different in two aspects: (1) PCA transform is used before clustering in this work; (2) In the work of Moore et al, only Euclidean distance was used in FCM, whereas in our work, four different similarity distances-SAD, ED, OPD, and TD-were used and new centroid sets were extracted.…”
Section: Clustering and Determination Of Centroid Setsmentioning
confidence: 99%
“…The following three-step clustering framework was adopted. The second step with Principal Component Analysis (PCA) transform and the third step based on more than one similarity measure constituted improvements on the classification method proposed by Moore et al [1,24].…”
Section: Classification Of Rrs (λ) Spectramentioning
confidence: 99%
See 1 more Smart Citation